Elementary Statistical Methods - Prasad, Sahana; Springer (2023)
This is the first book of two volumes covering the basics of statistical methods and analysis. Significant topics include concepts of research and data analysis, descriptive statistics, probability and distributions, correlation and regression, and statistical inference. The book includes useful examples and exercises as well as relevant case studies for proper implementation of the discussed tools. This book will be a valuable text for undergraduate students of statistics, management, economics, and psychology, wanting to gain basic understanding of statistics and the usage of its various concepts.
Intro
Preface
Acknowledgements
Contents
About the Author
List of Figures
List of Tables
1 Basic Concepts in Research and Data Analysis
1.1 Introduction: Understanding Data and a Few Terminologies
1.2 Scales of Measurement
1.3 Representing Data-Graphs and Charts
1.4 Box Plot, Stem and Leaf Diagrams
References and Research Articles
2 Measures of Central Tendencies
2.1 A Note on Summation
2.2 Partition Values
2.3 Measures of Dispersion
2.4 Understanding Standard Deviation and Variance
2.5 Coefficient of Variation CV 2.6 Lorenz Curve and Gini Coefficient [11]
References and Research Articles
3 Probability and Distributions
3.1 Introduction: Probability and Uncertainty
3.2 Some Basic Terminologies
3.3 Probability Definitions
3.4 Summary of Basic Probability Rules
3.5 Bayesian Basics
References and Research Articles
4 Hypothesis Testing
4.1 Introduction: Hypothesis
4.2 Parametric and Non-parametric Tests
4.3 ANOVA
4.4 Post Hoc Tests
4.5 Non-parametric Tests
Other References
5 Correlation and Regression
5.1 Introduction: Correlation
5.2 Regression
Includes bibliographic reference
Keywords: Electronic Books -- Statistics